Respon Pemberian POC Jakaba dan POP Feses Ayam Terhadap Pertumbuhan Dan Produksi Tanaman Timun Suri - Fitri Mutiara Syaqinah; Bambang Surya Adi Syahputra; Yunida Berlian (UNIVERSITAS LABUHANBATU, 2026)
This study was conducted at Jl. Young Panah Hijau Gg. Mesjid Nurul Hidayah, Lingkungan IV, Marelan District, Medan City, North Sumatra, from March to July 2025. The purpose of the study was to evaluate the response of muskmelon (Cucumis melo L. var. reticulatus Naudin) after application of Jakaba Liquid Organic Fertilizer (POC) and chicken manure Solid Organic Fertilizer (POP). The experiment was used Complete Randomized Block Design (CRBD) with two treatment factors namely; POC Jakaba (J0 = without POC, J1 = 250 ml/polybag, J2 = 500 ml/polybag, J3 = 750 ml/polybag) and chicken manure POP (A0= without POP, A1=500 g/polybag, A2 = 1000 g/polybag, A3 = 1500 g/polybag), with three replications, resulting in a total of 48 plots. The parameters were measured plant length, stem diameter, fruit length and diameter, and fruit weight per sample and per plot. The results were showed that Jakaba POC had a significantly effect on plant length, stem diameter, and fruit weight/plot, respectively. For chicken fesses POP, there was no significantly effect on the parameters of stem diameter, fruit length, and fruit diameter, but a significant effect on the parameters of plant length, fruit weight/sample, and fruit weight/plot. The interaction between Jakaba POC and chicken fesses POP had no significantly effect on all parameters. It can be concluded that the chicken fesses POP was good at a dose of 1000 grams/polybag as compared to other treatments. While Jakaba POC was better at 500 mL/polybag. Keywords: Jakaba POC, chicken manure POP, growth, yield, timun suri